Perbandingan Hasil Belajar Matematika Siswa dengan Menggunakan Model Pembelajaran Kooperatif antara Tipe TGT (Teams Games Tournament) dan Tipe NHT (Numbered Head Together) Ditinjau dari Kecerdasan Interpersonal Siswa - Syarifatunnisa; Suradi; Awi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research was quasi-experimental which aims to know the difference between students' mathematics learning outcomes who are taught by using cooperative learning model TGT type and students' mathematics learning outcomes who are taught by using cooperative learning model NHT type viewed from students’ interpersonal intelligence. The population in this research was Ten-grade students. The sample consisted of two classes, namely class X MIA 1 as first treatment class taught by using TGT learning model and class X MIA 2 as second treatment class taught by using direct NHT learning model selected by cluster random sampling technique. The variables in this research were cooperative learning model, students’ interpersonal intelligence, and mathematics learning outcomes. The research instruments used were observation sheets, questionnaires about students’ interpersonal intelligence, and mathematics learning outcomes tests. The data obtained were analyzed by using descriptive analysis and inferential analysis through Two Way ANOVA. Based on the result of the Two Way ANOVA, it was found that there is no difference between students' mathematics learning outcomes who are taught by using cooperative learning model TGT type and students' mathematics learning outcomes who are taught by using cooperative learning model NHT type viewed from students’ interpersonal intelligence.